Efek Crosslinker terhadap Performa Komposit Selulosa Bakteri – Ekstrak Daun Kembang Sepatu ( Hibiscus rosa- Sinensis L ) - Egidia Mayendra; Minda Azhar; Indang Dewata; Ananda Putra (Departemen Kimia FMIPA UNP, 2021)
Abstract — Bacterial cellulose can be applied in various fields such as biomedical fields, separation membranes, artificial blood vessels, and substrates for tissue engineering cartilage. Bacterial cellulose still has low mechanical properties, so a bacterial cellulose composite with hibiscus leaf extract (KSB-EDKS) is formed to obtain new, better materials. The purpose of this study was to determine the effect of adding starch as a crosslinker, on the mechanical, physical, and structural properties of KSB-EDKS. Bacterial cellulose is produced from a mixture of coconut water, sugar and urea. Then fermented with acetobacter xylinum for 14 days. Bacterial cellulose formed in composites with hibiscus leaves is called bacterial cellulose extract of hibiscus leaves (KSB-EDKS). KSB-EDKS will be characterized by testing tensile strength, moisture content, structural analysis using FTIR and determining the degree of crystallinity using XRD. The addition of a crosslinker can reduce the percentage of KSB-EDKS water content. The best tensile strength test results were KSB-EDKS added with 3% tapioca flour solution with a value of 38.3 MPa, the FTIR spectrum showed that the functional groups in cellulose had just shifted in the range of the same wave number values and for the degree of crystallinity the addition of starch as crosslinker can reduce the degree of crystallinity in KSB-EDKS. Keywords — Bacterial cellulose, Composite, Crosslinker, Hibiscus leaves